Aesthetical and Political Aspects of the Relationship between Literature and Ideology in Albania in Dictatorship and in Post-Communism - Shatro, Bavjola (Richtmann Publishing, 2011)
This paper focuses on the relationship between literature and ideology in a former communist country, namely in Albania.The relationship between literature and ideology in Albania resulted in both aesthetical and political consequences, during communismand also in post-communism.In the aesthetical point of view this relationship damaged the previous literary tradition in Albania, it created a limitedlinguistic model in all literary genres, and it formed a false concept of Realism to the readers and an unlikely perception of the socialreality itself. This relationship between literature and ideology caused the denigration of the dissenting authors and their expulsion fromthe literary history even though they were representatives in the Albanian literature.In the social and political point of view it strongly supported the war of classes through imprisonments, internal exile of thewriters and their families, and even the execution of the writers that were considered enemies of the Party and people.Even presently in post-communist Albania there are still opened debates on the political persecutions of the writers based onlyon their ideological disagreement with the regime, but also about the other side of the issue, which is the possible connection between writersand the State Apparatuses where they might have served during dictatorship.These phenomena will be analyzed basing on methodological lines that are mainly culturologic ones.